(untitled) (Ibrahim Cardiac Medical Journal, 2019)
Background & objective: To see the relationship between preeclampsia and iron parameters (serum iron, serum ferritin and total iron binding capacity). Methods: The present case-control study was carried out in the Department of Obstetrics & Gynaecology, Dhaka Medical College Hospital (DMCH), Dhaka in collaboration with the Department of Biochemistry, BSMMU, Dhaka over a period of 1 year from July 2012 to June 2013 Pregnant women with preeclampsia admitted in the above-mentioned hospital were considered as case, while the pregnant women without preeclampsia were included as control. A total of 60 women-31 cases and 29 controls were purposively included in the study. The exposure variables were serum ferritin, serum iron and total iron binding capacity (TIBC), while the outcome variable was preeclampsia. The serum iron level > 100 μg/L was considered as hyperferritenemia. Result: Nearly two-thirds of the women were in their 2nd decades of life belonged to lower socioeconomic class. The body mass index was also fairly comparable between the groups with most women having normal BMI. No significant difference was observed between the groups with respect to obstetric variables as well. Level of haemoglobin and hematocrit were also identically distributed between groups. The result showed that a significantly higher proportion (35.5%) preeclamptic women had elevated serum ferritin (> 100 μg/L) as opposed to 10.3% of the control group (p = 0.021). The risk of developing raised serum ferritin in women with preeclampsia was estimated to be 4-fold (95% CI =1.2 – 19.4) higher than that in the normal pregnant women. Analyses also revealed that women with severe preeclampsia had a higher mean serum ferritin (207.3 ± 44.1 ng/ml) than the women with mild preeclampsia (41.7 ± 2.7) and an even higher level compared with the normal pregnant women (21.7 ± 1.4 μg/ml) (p = 0.001). Similar result was observed in serum iron with greater the severity, higher is the level of serum iron (p = 0.067). Conversely, the serum total iron binding capacity (TIBC) was decreased with severity of preeclampsia (p = 0.058). Conclusion: The study concluded that women with preeclamsia might be associated with higher serum ferritin, higher serum iron and lower serum TIBC although it is not known whether the rise in serum ferritin and serum iron precedes or contributes to the clinical manifestations of preeclampsia. Ibrahim Card Med J 2017; 7 (1&2): 64-69